1999
DOI: 10.1116/1.591121
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of InGaP/GaAs heterointerface quality by controlling AsH3 flow conditions

Abstract: Articles you may be interested inHigh-quality 1.3 μm-wavelength GaInAsN/GaAs quantum wells grown by metalorganic vapor phase epitaxy on vicinal substrates Appl. Phys. Lett. 99, 072116 (2011); 10.1063/1.3623478 Structural characterization of metal organic vapor phase epitaxy grown GaInNAs quantum well with InGaAs and GaNAs barriers

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…The arsenic carry-over discussed earlier may be more pronounced for longer exposure to AsH 3 before the InP growth, and higher growth temperature of InP may enhance Ga diffusion from InGaAs in the growing i-InP to compensate the local tensile strain in InGaAs caused by heavy carbon-doping. In the growth of InGaP on GaAs, longer exposure of GaAs to AsH 3 caused excess arsenic on the GaAs surface, which formed donor-like defects in the growing InGaP [15]. Similarly in the growth of InP-on-InGaAs, longer exposure to AsH 3 may also cause excess arsenic on the InGaAs surface, which causes arsenic carry-over.…”
Section: N-inp-on-p-ingaas Diodementioning
confidence: 95%
“…The arsenic carry-over discussed earlier may be more pronounced for longer exposure to AsH 3 before the InP growth, and higher growth temperature of InP may enhance Ga diffusion from InGaAs in the growing i-InP to compensate the local tensile strain in InGaAs caused by heavy carbon-doping. In the growth of InGaP on GaAs, longer exposure of GaAs to AsH 3 caused excess arsenic on the GaAs surface, which formed donor-like defects in the growing InGaP [15]. Similarly in the growth of InP-on-InGaAs, longer exposure to AsH 3 may also cause excess arsenic on the InGaAs surface, which causes arsenic carry-over.…”
Section: N-inp-on-p-ingaas Diodementioning
confidence: 95%
“…Besides PL, several other techniques, like X-ray diffraction [12,16,[18][19][20], electrical methods [24,25] scanning tunneling spectroscopy [26] were employed to investigate the properties of the interlayer at the GaAs-on-InGaP interface. Transmission electron microscopy (TEM) was applied in some works to get information on the overall structure of the InGaP/GaAs samples [6,8,19,20,27,28], but detection and information right of the interlayer was not reported apart from the paper by Hsieh et al where the interlayer was detected by Scanning TEM (STEM) [7]. However, the exact identification and evaluation of the interlayer composition by TEM seems to be missing.…”
Section: Introductionmentioning
confidence: 96%
“…Generally, no extra interlayer is present at the normal InGaPon-GaAs interface. Only a very few papers reported on its presence [6,22]. Photoluminescence (PL) has shown that an emission at a wavelength longer than the ones of GaAs and InGaP is always associated with the extra interlayer [7,10,[12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…6 The most common recipe used to reduce anion intermixing is to make a growth interruption at the interface during which the arsenide surface is exposed to a phosphorus flux or vice versa. [7][8][9] This kind of procedure then raises the question of the reactivity of an arsenide surface to a phosphorus flux and of a phosphide surface to an arsenic one. The most extensively studied case is that of InP with As since it occurs directly when the InP substrate oxide removal is performed under an As overpressure.…”
mentioning
confidence: 99%